Implementation Character Learning Model in Hotel Practice Learning Based on Minahasa Local Wisdom for Students of Tourism Department - Bernadain D. Polii; Diane Tangian; Agustinus Lumettu (AIBPM Publisher, 2020)
The purpose of the research of character learning models in the learning of hospitality practices based on local wisdom for students of the Department of Tourism is that students have attitudes and behaviors that are in harmony with the values / rules that apply and preserve and develop the noble values of local culture in order to support regional and national development especially in the field of Hospitality. The research method used in this research is a qualitative approach method. This research was conducted at Manado State Polytechnic. In this study, the primary data were obtained by researchers from the results of in-depth interviews with key informants, namely: Head of the Study Program, Heads of Laboratoris, Lecturers, employees and students. To get more in-depth data, the researchers also observed directly when the students practiced in each subject. After the data collected is analyzed using inductive techniques including data reduction, data presentation, and data verification (conclusion drawing / verification). In the practice learning process, students are provided with materials in accordance with the job sheets that have been made. As a result of observations starting from the preparation of the equipment, there are still some students who arrive late and, are not disciplined in the use of time. At the time of the group division, there were still some students who only wanted to be in groups with their close friends.The implementation of character learning based on local wisdom in the study of hospitality practices starts from the making of this local wisdom into the quality culture of universities or institutions. In this institution there are individuals as internal customers and external customers who need one another to realize the vision and mission of the university especially the institutional level. Formulation of character values based on local wisdom of Minahasa Si Tou Tu Mou Ti Mou Tou lossistiry of Tou Ente ' which means firm in principle, highly disciplined, honest, open, democratic. Tou Nga'asan which means smart, always wants to know, tries to catch the right one. Tou Sama ' which means a religious attitude, tolerant, like to help